Upaya Pengembangan Kreatifitas Istri Nelayan dalam Mengolah Makanan Berbahan Dasar Ikan di Kelurahan Boneoge Kab. Donggala - Fauzan Abdul Latif (Yayasan Literasi Sains Indonesia, 2022)
Donggala Regency as an indicator, namely the performance of the community as measured by the poverty level and initially showed that during the 2015-2019 period, the poverty rate in Donggala Regency increased from 54.17 thousand people in 2015 to 55.83 thousand people in 2019. This is a lot shows that both poor households (RTM) and the number of poor people moving above the poverty line are increasing. The purpose of this project is to fulfill the youth program in an effort to empower, especially fishermen's wives in utilizing marine products in the form of fish which can be processed into various types of food and used as an additional effort to increase income and welfare of life, as well as educate online marketing methods so that products can be recognized by people outside the region. Activity Program Development Strategy using online and offline methods by educating how to market and developing the creativity of fishermen's wives in processing these marine products. The marketing and publication strategis that will be carried out to support the implementation of this project use onlie and offline methods. The product publication strategy is carried out online by utilizing ecommerce (Shopee & Tokopedia) and social media (Instagram, Tik Tok, and Facebook). Meanwhile, the offline stratey for product to be made is targeting the main target market, namely the people of Donggala regency. The results of the team-based project show that fishermen's wives gain general knowledge about how to manage marine products in general which are broad to be applied in the field as professional management experts and entrepreneurs in the field of marine products management large